Diseño De Un Protocolo Para La Colecta De Células Madre A Partir Del Cordón Umbilical De Neonatos Caninos (2022)
Stem cells are undifferentiated, immature, self-renewing, and capable of generating one or more types of differentiated cells. These cells can divide indefinitely while always maintaining a stable population of stem cells and differentiate into different types of specialized cells of an adult organism. There are several sources of stem cells, such as umbilical cord blood, bone marrow, peripheral blood, skin, teeth, placenta, embryos, etc. (Evans and Kaufman 1981, Das et al 2008).